ANALYSIS OF THE INFLUENCE OF COSO'S INTERNAL CONTROL SYSTEM ON INVENTORIES OF A COMPANY - Winda Atikah Fanani; Juliyawita Dwi Iswara; Dian Hakip Nurdiansyah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to obtain evidence regarding the internal control system in PT. Boltz Indonesia regarding the inventory and system at the company whether it is in accordance with the procedures set by COSO or not. This research uses descriptive qualitative method. The data used in the research at the PT is primary data and also secondary data. Methods Data collection was carried out through direct interviews with Supervisors and HRD as well as observation. The results of the study show that PT Boltz Indonesia is almost in accordance with the procedures implemented by COSO starting from supplies, systems at the company and software at the company. This study examines the inventory at PT. Boltz Indonesia and also look at the risks that occur in the company and the results of research that have been carried out show that the COSO internal control system at PT. Indonesian Boltz. Fairly in accordance with the internal control components contained in COSO related to inventory although there are indeed some that are not in accordance with the COSO internal control system.